Perlindungan Hukum Bagi Investor Terkait Pembubaran Badan Hukum Reksa Dana - I Gede Satyawan Pradnya Wiguna; I Nyoman Budiartha; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2021)
Mutual funds are investment instruments regulated in regulation number 23/POJK/04/2016 concerning mutual funds, as a guide for investment managers, protecting the rights of investors, investors are not careful in choosing mutual fund products and determining the right and safe investment manager so that legal protection is needed for Mutual Fund Investors. The purposes of this study are to analyze the legal consequences for investors related to the dissolution of a mutual fund legal entity and legal protection for mutual fund investors related to the dissolution of a mutual fund legal entity. The method used is normative legal research with a statutory approach. The technique of collecting legal materials is done through recording and documentation studies. Primary and secondary sources of legal materials are used as sources of legal materials in this study. Then, the legal materials and data are managed using interpretation analysis. The results of the study show that the legal consequences for investors related to the dissolution of the mutual fund managing legal entity are regulated in article 50 of the OJK Regulation if the mutual fund product is dissolved the investor cannot resell after the dissolution of the mutual fund product, protection for mutual fund investors is related to the dissolution of the mutual fund managing legal entity, if there is a loss to the mutual fund product caused by the investment manager, the investment manager must be responsible for the loss due to his actions